(untitled) (Research, Society and Development, 2024)
Sport plays a crucial role in human development, serving as a powerful tool for socialization and fostering a sense of community. In the school context, Physical Education goes beyond physical activity, promoting inclusion, respect, and cooperation among students from diverse backgrounds and abilities. Thus, sport establishes itself as a transformative agent, contributing to the formation of citizens aware of their social role and fostering inclusive education. The objective is to identify and analyze existing studies on the relationship between sport and inclusion in the school environment, as well as to understand the impacts of this interaction on the social, emotional and educational development of students. This study, based on a bibliographic review, aimed to analyze the relationship between sport and inclusion in schools, focusing on social, emotional, and educational impacts. The main findings highlighted the role of sport in promoting teamwork, empathy, and respect for differences, as well as emotional benefits such as self-esteem, resilience, and confidence. Barriers to implementing inclusive sports practices were also identified, including structural, pedagogical, and cultural challenges. Overcoming these obstacles requires a holistic approach that includes educator training, resource adaptation, and awareness of diversity and equity. When strategically applied, sport has the potential to transform the school environment, making it more collaborative, inclusive, and equitable, contributing to the integral development of all students.